2019
DOI: 10.1007/s13202-019-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a naturally derived tannin extracts biopolymer additive in drilling muds for high-temperature well applications

Abstract: The formulations of drilling fluids using conventional clays are often faced with difficulties in the control of rheology, filtration and gelation, owing to the flocculation of the clay at the temperature above 250 °F. In this study, tannins were extracted from the bark wastes of Rhizophora Mucronata spp. (RMTE) and used as a deflocculant to formulate water-based muds (WBMs). The efficacy of reducing the gelation and viscosity of WBMs with the extracted RMTE was compared with commercial Modified Desco Tannin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…For PAC LV, it displayed a negative effect on both the 10 s and 10 min gels, especially the 2.0 g concentration and the difference between these gels exceeds 10 lb/100ft 2 . This could need extra pump pressure to break the gels when changing from non-flow to flow conditions, which in turn can adversely affect pump efficiency and cause fractures in poor formations (Ismail et al 2019). It, therefore, holds that, if higher concentrations of PAC LV are introduced into the complex WBDF system as per this study, it might result in flocculation (Oseh et al 2019c, d).…”
Section: The Rheological Characteristics Of Wbdfs Investigated With Pmentioning
confidence: 81%
“…For PAC LV, it displayed a negative effect on both the 10 s and 10 min gels, especially the 2.0 g concentration and the difference between these gels exceeds 10 lb/100ft 2 . This could need extra pump pressure to break the gels when changing from non-flow to flow conditions, which in turn can adversely affect pump efficiency and cause fractures in poor formations (Ismail et al 2019). It, therefore, holds that, if higher concentrations of PAC LV are introduced into the complex WBDF system as per this study, it might result in flocculation (Oseh et al 2019c, d).…”
Section: The Rheological Characteristics Of Wbdfs Investigated With Pmentioning
confidence: 81%
“…The newly developed RMTE deflocculant was found to be temperature resistant and stable with high temperatures. Furthermore, Reference [61] studied the extraction of RMTE using various solvents and concluded that water is the safest solvent to use since it is safer and less costly than methanol and yields the most RMTE.…”
Section: Unmodified Tannin-based Deflocculantsmentioning
confidence: 99%
“…Second, the performance of TBD as a deflocculant, with and without thermal ageing treatment, is contrasted with each other by using a commercial deflocculant as a control agent [61]. According to [64], thermal ageing using hot rolling treatments reduces rheological parameters and thermal ageing statically raises the same parameters.…”
Section: High Temperature-tolerance Of Tannin-based Deflocculantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants the formation of indigestible PAC-protein complexes gives rise to the anti-feeding effect and protects the plants from herbivores [ 7 ]. Industrially, PAC extracts are still widely used in the leather industry [ 8 ], the adhesive industry [ 9 ], as additives to animal feed [ 10 ], the wine industry [ 11 ], as flocculants [ 12 , 13 , 14 ], and as mud-drilling additives [ 13 ]. Pharmacological properties include anti-oxidant activity [ 15 , 16 , 17 ], Alzheimer’s disease inhibition [ 18 ], anti-cancer activity [ 19 , 20 ], anti-diabetic [ 21 , 22 ], anti-microbial [ 23 , 24 ] and anti-cardiovascular diseases [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%